Does Hypoxia Decrease the Metabolic Rate? - Gu, Chenjuan; Jun, Jonathan C. (Frontiers in Endocrinology, 2018)
In some organisms and cells, oxygen availability influences oxygen consumption. In this review, we examine this phenomenon of hypoxic hypometabolism (HH), discussing its features, mechanisms, and implications. Small mammals and other vertebrate species exhibit “oxyconformism”, a downregulation of metabolic rate and body temperature during hypoxia which is sensed by the central nervous system. Smaller body mass and cooler ambient temperature contribute to a high metabolic rate in mammals. It is this hypermetabolic state that is suppressed by hypoxia leading to HH. Larger mammals including humans do not exhibit HH. Tissues and cells also exhibit reductions in respiration during hypoxia in vitro, even at oxygen levels ample for mitochondrial oxidative phosphorylation. The mechanisms of cellular HH involve intracellular oxygen sensors including hypoxia-inducible factors, AMP-activated protein kinase, and mitochondrial reactive oxygen species which downregulate mitochondrial activity and ATP utilization. HH has a profound impact on cardiovascular, respiratory, and metabolic physiology in rodents. Therefore, caution should be exercised when extrapolating the results of rodent hypoxia studies to human physiology.